Serosurvey of canine distemper virus in culpeo (Lycalopex culpaeus) and chilla (Lycalopex griseus) foxes of the Araucanía region, Chile - Hernández, Felipe A.; Surot, Dominique; Vallverdú, Antulemu; Cueva, Michelle; Aguirre, Isabel M.; Mancilla, Edith A.; Acosta-Jamett, Gerardo (Austral Journal of Veterinary Sciences, 2023)
Our goal was to assess whether free-ranging foxes have been exposed to canine distemper virus (CDV) in the Araucanía region in Chile. The study was conducted at three sites in rural areas where free-ranging foxes were trapped and bled from 2009 to 2012. We sampled two species of foxes: the culpeo (Lycalopex culpaeus) (n=13) and the chilla (Lycalopex griseus) (n=14). A serum virus neutralization assay was used to detect the presence and magnitude of functional systemic antibodies to CDV. Overall, CDV seroprevalence in culpeo and chilla foxes was 7.7 and 21.4%, respectively. Exposure to CDV did not differ among the sites. Despite the relatively low seroprevalence found in free-ranging foxes, the presence of CDV-seropositive dogs previously reported in rural sites nearby, suggests a potential risk of pathogen spill over from domestic dogs to foxes in the area.